2020
DOI: 10.3389/fncel.2019.00573
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Effect of Buspirone on the H-Reflex in Acute Spinal Decerebrated Mice

Abstract: Pharmacological treatment facilitating locomotor expression will also have some effects on reflex expression through the modulation of spinal circuitry. Buspirone, a partial serotonin receptor agonist (5-HT 1A), was recently shown to facilitate and even trigger locomotor movements in mice after complete spinal lesion (Tx). Here, we studied its effect on the H-reflex after acute Tx in adult mice. To avoid possible impacts of anesthetics on H-reflex depression, experiments were performed after decerebration in u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 82 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Moreover, it is likely that locomotor improvements are associated with improved motoneuron reflex excitability, as suggested by Develle and Leblond. These authors showed that the same single dose of Buspirone could increase frequency-dependent depression of the H-reflex as compared with saline injection [28] in mice after T8 complete spinal lesion. Moreover, Jin et al [29] showed that the same 5-HT 1A agonist can improve forelimb locomotion by increasing reaching and grasping accuracy as early as 2 weeks post C4 injury in adult female rats [29] using a lower dose of Buspirone (1-2 mg/kg/day, i.p.).…”
Section: Locomotor Effects Of 5-ht 1a Agonists Pharmacology In Scimentioning
confidence: 98%
“…Moreover, it is likely that locomotor improvements are associated with improved motoneuron reflex excitability, as suggested by Develle and Leblond. These authors showed that the same single dose of Buspirone could increase frequency-dependent depression of the H-reflex as compared with saline injection [28] in mice after T8 complete spinal lesion. Moreover, Jin et al [29] showed that the same 5-HT 1A agonist can improve forelimb locomotion by increasing reaching and grasping accuracy as early as 2 weeks post C4 injury in adult female rats [29] using a lower dose of Buspirone (1-2 mg/kg/day, i.p.).…”
Section: Locomotor Effects Of 5-ht 1a Agonists Pharmacology In Scimentioning
confidence: 98%